REFORMULASI KAIDAH MAKKĪ – MADANĪ; Studi Ayat-Ayat Hubungan Antarumat Beragama: REFORMULATION OF THE MAKKĪ–MADANĪ PRINCIPLE; A Study of Interreligious Relation Verses - Muhammad Labib Syauqi; Nur Arfiyah Febriani; Ade Irwansyah (Jurnal Bimas Islam, 2026)
The principles of Ulum al-Qur'an operationalize the concept of Madanī as verses that abrogate (naskh) the Makkī revelations. This perspective gives rise to various problems, particularly concerning verses addressing interreligious relations, in which verses advocating peace and coexistence with adherents of other religions are considered abrogated by the so-called “sword verses” revealed subsequently. The reconceptualization of the Makkī–Madanī framework has therefore become urgent in order to generate an interpretation more compatible with the modern world. Accordingly, this study seeks to reformulate the Makkī–Madanī principles by employing the theoretical framework of the historicity of the Qur’an. The findings demonstrate that the concept that should be foregrounded is “prioritizing the Makkī and deferring the Madanī,” since the Makkī constitutes the fundamental principle, whereas the Madanī represents its derivative branch